Analysis of Corporate Srategy in The Development of Micro, Small, and Enterprises (MSMEs) - Nilna Nada Hudayah; Hendra Sukmana (Indonesian Journal of Public Policy Review, 2022)
The MSME sector in Indonesia is one of the driving sectors of economic activity. Sidoarjo Regency became one of the regencies that have a number of MSME potential that has superior value so that Sidoarjo Regency gets the nickname as the city of INDONESIAN MSMEs. With this potential, if not accompanied by good development will be a problem in the MSME sector. Through corporate strategy, MSME actors will be given a form of assistance in terms of development. However, in its implementation there is a problem that is the lack of interest and mindset that has not been formed for entrepeneurship. The purpose of this study is to find out and describe and analyse corporate strategy in the development of MSMEs in Sidoarjo Regency. Qualitative descriptive research methods. Determination of informants is done by purposive sampling method data analysis techniques through data collection, data reduction, data presentation, and conclusion withdrawal. The results of this study show that the corporate strategy in the development of MSMEs is in accordance with the conditions on the ground. This condition is proven by the implementation of the science alms program as an corporate strategy.